Transient Global Amnesia and Neurological Events: The Framingham Heart Study - Romero, Jose R.; Mercado, Melissa; Beiser, Alexa S.; Pikula, Aleksandra; Seshadri, Sudha; Kelly-Hayes, Margaret; Wolf, Philip A.; Kase, Carlos S. (Frontiers in Neurology, 2013)
Background/ objective: Transient global amnesia (TGA) is a temporary amnestic syndrome characterized by lack of other focal neurological deficits. Cerebrovascular disease, migraine and seizures have been suggested as underlying mechanisms. TGA may be a risk factor for cerebrovascular or other neurological events. We studied the relation of TGA, vascular risk factors, brain magnetic resonance imaging (MRI) indices of subclinical ischemia and neurological events in a community-based sample. Design/setting: A total of 12 TGA cases were ascertained using standard criteria by experienced neurologists, and matched to 41 stroke- and seizure-free controls. Vascular risk factors, brain MRI findings, and subsequent cerebrovascular or seizure events were compared in cases and controls. Participants: Framingham Heart Study (FHS) original and offspring cohort participants were included. Results: No significant differences between the groups were observed in the prevalence of vascular risk factors, or brain MRI measures. Few incident stroke/transient ischemic attacks (TIA) (1 event among the cases and 4 in controls) or subsequent seizures occurred in either group. Head CT during the acute event (n=11) and brain MRI (n=7) were negative for acute abnormalities. Electroencephalograms (EEG) (n=5) were negative for epileptiform activity. Extracranial vascular studies were negative for significant stenosis in all cases. Conclusions: In our community-based study TGA was not related to traditional vascular risk factors, or cerebrovascular disease. However, our study is limited by small sample size and power, and larger studies are required to exclude an association.